Clinical study of 182 cases of myocardial infarction - Jerí V., Raúl (1947)
In 9896 medical records of several Internal Medicine hospital Dos de Mayo, Central Police and Arzobispo Loayza, we found 1,724 organic heart disease (16.51%), 474 sclerosis of the coronary arteries (27.53% of the heart) and these latest 182 cases of myocardial infarction (38.31%).